Delayed macrophage targeting by clodronate liposomes worsens the progression of cytokine storm syndrome - Khanna, Kunjan; Eul, Emily; Yan, Hui; Faccio, Roberta (Frontiers in Immunology, 2024)
Excessive macrophage activation and production of pro-inflammatory cytokines are hallmarks of the Cytokine Storm Syndrome (CSS), a lethal condition triggered by sepsis, autoimmune disorders, and cancer immunotherapies. While depletion of macrophages at disease onset protects from lethality in an infection-induced CSS murine model, patients are rarely diagnosed early, hence the need to characterize macrophage populations during CSS progression and assess the therapeutic implications of macrophage targeting after disease onset. In this study, we identified MHCII+F4/80+Tim4- macrophages as the primary contributors to the pro-inflammatory environment in CSS, while CD206+F4/80+Tim4+ macrophages, with an anti-inflammatory profile, become outnumbered. Additionally, we observed an expansion of Tim4- macrophages coinciding with increased hematopoietic stem progenitor cells and reduction of committed myeloid progenitors in bone marrow and spleen. Critically, macrophage targeting with clodronate liposomes at disease onset prolonged survival, while their targeting in mice with established CSS exacerbated disease severity, leading to a more dramatic loss of Tim4+ macrophages and an imbalance in pro- versus anti-inflammatory Tim4- macrophage ratio. Our findings highlight the significance of timing in macrophage-targeted interventions for effective management of CSS and suggest potential therapeutic strategies for diseases characterized by uncontrolled inflammation, such as sepsis.